Nomogram of paediatric male urethral size: A systematic review. Issue 1 (February 2022) - O'Hagan, Lomani A.; Larsen, Peter D.; Nataraja, Ramesh M.; Pacilli, Maurizio; Taghavi, Kiarash
Summary: Introduction: Knowledge of the normal size of the urethral meatus in boys is important for safely performing urethral catheterization and fundamental to the diagnosis and treatment of paediatric urological conditions. However, clinicians often rely subjectively on previous experience and clinical judgement, rather than a robust evidence-base. A systematic review of the literature was undertaken to define the calibre of the male urethral meatus in paediatric age-groups. Methods: The MEDLINE and EMBASE databases were systematically searched from inception to December 2020 for studies measuring meatal calibre in boys up to 16 years of age. Google Scholar searches along with forward and backward citation tracking identified additional studies. Studies of subjects >16 years, females, or patients with urethral diseases were excluded. Results: Nine articles (2084 paediatric subjects) were included in the final review. Mean meatal calibre increases non-linearly with age, with accelerated growth occurring during infancy (mini-puberty) and adolescence (puberty). Meatal calibre can be approximately grouped by age as follows: neonate (6-10Fr); infant (10-12Fr); child (12-14Fr); and adolescent (14-18Fr). There is substantial individual variability for same-aged children. Meatal calibre has been independently related to height, weight, and penile size, but the effects of ethnicity and circumcision remain unclear. Conclusions: The evidence-base for this fundamental aspect of paediatric urology includes only a few low-quality studies and is largely derived from one early study of circumcised American boys. Further studies are warranted to establish normative urethral size values based on rigorous, contemporary data with known dependent variables also included.